MicroRNA‐139‐5p confers sensitivity to antiepileptic drugs in refractory epilepsy by inhibition of MRP1. (21st November 2019) - Wang, Li; Song, Lifang; Chen, Xiaoyi; Suo, Junfang; Ma, Yanli; Shi, Jinghe; Liu, Kai; Chen, Guohong
Abstract: Aim: Drug resistance is an intractable issue urgently needed to be overcome for improving efficiency of antiepileptic drugs in treating refractory epilepsy. microRNAs (miRNAs) have been proved as key regulators and therapeutic targets in epilepsy. Accordingly, the aim of the present study was to identify a novel differentially expressed miRNA which could improve the efficiency of antiepileptic drugs during the treatment of refractory epilepsy. Methods and Results: Serum samples were collected from children with refractory epilepsy. An in vivo refractory epilepsy model was developed in SD rats by electrical amygdala kindling. We identified that miR‐139‐5p was decreased and multidrug resistance‐associated protein 1 (MRP1) was remarkably upregulated in the serum samples from children with refractory epilepsy and the brain tissues from rat models of refractory epilepsy. After phenobarbitone injection in rat models of refractory epilepsy, the after discharging threshold in kindled amygdala was detected to screen out drug‐resistant rats. Dual‐luciferase reporter gene assay demonstrated that MRP1 was a target of miR‐139‐5p. In order to evaluate the effect of miR‐139‐5p/MRP1 axis on drug resistance of refractory epilepsy, we transfected plasmids into the hippocampus of drug‐resistant rats to alter the expression of miR‐139‐5p and MRP1. TUNEL staining and Nissl staining showed that miR‐139‐5p overexpression or MRP1 downregulation could reduce the apoptosis and promote survival of neurons, accompanied by alleviated neuronal damage. Conclusion: Collectively, these results suggest an important role of miR‐139‐5p/MRP1 axis in reducing the resistance of refractory epilepsy to antiepileptic drugs.